Role of N6-methyladenosine Modification in Cardiac Remodeling - Choy, ManTing; Xue, Ruicong; Wu, Yuzhong; Fan, Wendong; Dong, Yugang; Liu, Chen (Frontiers in Cardiovascular Medicine, 2022)
Cardiac remodeling is the critical process in heart failure due to many cardiovascular diseases including myocardial infarction, hypertension, cardiovascular disease and cardiomyopathy. However, treatments for heart failure focusing on cardiac remodeling show relatively limited effectiveness. In recent decades, epitranscriptomic modifications were found abundantly present throughout the progression of cardiac remodeling, and numerous types of biochemical modifications were identified. m6A modification is the methylation of the adenosine base at the nitrogen-6 position, and dysregulation of m6A modification has been implicated in a wide range of diseases. However, function of m6A modifications still remain largely unknown in cardiac diseases, especially cardiac remodeling. LncRNAs are also shown to play a vital role in the pathophysiology of cardiac remodeling and heart failure. The crosstalk between lncRNAs and m6A modification provides a novel prospective for exploring possible regulatory mechanism and therapeutic targets of cardiac remodeling. This review summarizes the role of m6A modification in cardiac remodeling in the current researches.